Burnout syndrome in nursing professionals during the Covid-19 pandemic in a municipality in the Southwest of Pará (Research, Society and Development, 2021)
Burnout syndrome (BS) is present in the lives of many health professionals, as they are exposed to different situations of stress in the work environment. The objective of the research was to describe the BS in nurses and nursing technicians working in Basic Health Units and Hospitals in a city in the Southwest of Pará. The sample consisted of 109 professionals, of which 49 were nurses and 60 nursing technicians. Two data collection instruments were used: sociodemographic and health questionnaire and the Maslach Burnout Inventory (MBI) questionnaire. To verify the association between the classification of Burnout syndrome and sociodemographic data, the Chi-Square or Fisher's exact test was used, according to the test assumptions. SB was present in 12.8% of the participants, of which 64.3% are nurses. Regarding the dimensions of the MBI, 59.9% had low professional achievement, 42.2% had high emotional exhaustion and 58.7% had moderate depersonalization. The emotional exhaustion dimension was the one with the highest percentage at the high level, when compared to depersonalization (27.5%) and professional fulfillment (2.8%). No statistical differences were identified in the association of dimensions with sociodemographic data. Professional exhaustion was associated with undergoing treatment for depression (p=0.05), practicing physical activity (p=0.01), feeling about work (p=0.04) and having suffered some type of violence at work (p=0.03). Depersonalization was associated with religion (p=0.01), feeling towards work (p=0.02), having suffered some type of violence at work (p=0.01) and believing to be affected by BS (p =0.03), while personal fulfillment was associated with religion (p=0.03). The development of actions aimed at promoting the health and well-being of these professionals is important considering the Covid-19 pandemic moment.